Analytical political philosophy : from discourse, edification - Braybrooke, David (Toronto studies in philosophy., 2006)
"The analytic movement has long been the dominant philosophical tradition in English-speaking countries. In Analytical Political Philosophy: From Discourse, Edification, Canadian philosopher David Braybrooke explores this movement by bringing together some of his earlier free-standing studies of the concepts of needs, rights, and rules. He combines the results with an analytical account of how to deal with consequences and thus, arrives at a program for public policy, comparable in generality at least and in trenchancy to the programs offered by Rawls, Nozick, and Gauthier."--Jacket